2004
DOI: 10.1021/jp0312971
|View full text |Cite
|
Sign up to set email alerts
|

Polyol Process Synthesis of Monodispersed FePt Nanoparticles

Abstract: Monodispersed FePt nanoparticles are synthesized by reduction of iron(II) acetylacetonate and platinum(II) acetylacetonate with 1,2-hexadecanediol as the reducing reagent in the polyol process. As-prepared FePt nanoparticles are chemically disordered with fcc phase. Transmission electron microscopy (TEM) images show a self-assembled particle array with an average particle size of 3 nm and a standard deviation about 10%. The transformation from chemically disordered fcc to chemically ordered L10 phase is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 11 publications
1
82
0
11
Order By: Relevance
“…Toda et al [146] reported that oxygen adsorption increases in the case of changing of the electronic structure of Pt induced by a transition metal, and then the O-O bond is weakened. For this purpose, various platinum-based bimetallic catalysts, such as Pt-Ni [147,148], Pt-Co [149,150], Pt-Fe [151,152], Pt-Cr [153,154], Pt-Cu [155,156], Pt-V [157,158], Pt-Mn [159], Pt-Bi [35], Pt-Te [160] have been reported. It can be clearly emphasized that modified-platinum catalysts display 1.5-3 times higher catalytic activity than that of pure platinum catalyst.…”
Section: Orr Activity On Various Carbon Supported Nanoparticles Prepamentioning
confidence: 99%
“…Toda et al [146] reported that oxygen adsorption increases in the case of changing of the electronic structure of Pt induced by a transition metal, and then the O-O bond is weakened. For this purpose, various platinum-based bimetallic catalysts, such as Pt-Ni [147,148], Pt-Co [149,150], Pt-Fe [151,152], Pt-Cr [153,154], Pt-Cu [155,156], Pt-V [157,158], Pt-Mn [159], Pt-Bi [35], Pt-Te [160] have been reported. It can be clearly emphasized that modified-platinum catalysts display 1.5-3 times higher catalytic activity than that of pure platinum catalyst.…”
Section: Orr Activity On Various Carbon Supported Nanoparticles Prepamentioning
confidence: 99%
“…polyvinylpyrrolidone) and microwave heating, various types of nanoparticles have been synthetized . Metals (Ni [6,7], Co [8,9], Cu [10], Pd [11], Ag [12][13][14], Pt [15][16][17], Au, [18,19] ), alloys [9,[19][20][21][22][23][24][25], oxides (MgO, TiO 2 , ZnO, SnO 2 , Gd 2 O 3 , Fe oxides and ferrites, hydroxyapatite [26][27][28][29][30][31][32][33][34][35], metal-polymer nanocomposites [36], supported metal catalysts [37][38][39][40], have been designed.…”
Section: Direct Methods For the Preparation Of Nanoparticlesmentioning
confidence: 99%
“…5,6 A plethora of techniques exist for the synthesis of FePt nanoparticles including coreduction of precursors, single source molecular precursors, and solid-state reactions. [7][8][9][10][11][12][13][14][15][16] However, few have considered ternary alloys with Fe and Pt. Most reports focus on the addition of a third element dopant keeping the stoichiometry between Fe and Pt fixed with the purpose of reducing ordering temperature.…”
Section: Introductionmentioning
confidence: 99%